1F.002 Pre-hospital care knowledge among first responders in Delhi national capital region, India. (14th March 2021) - Chakraborty, Smita; Chhabra, Harvinder Singh; Sachdev, Gaurav; Phadke, Vandana; Sharawat, Rajesh; Joseph, Teena Elsa
Abstract : Background: Despite many improvements, pre-hospital care is known to be inconsistent, unreliable or deficient in India that causes high mortality and morbidity in accident victims. Bystanders hesitate to provide first-aid due to multiple reasons. Bystanders and first aiders are not adequately trained to handle all aspects of trauma including extrication, evacuation, transfer, cardiopulmonary resuscitation, management of bleeding, and protection of the spine. Evidence says that improper pre-hospital care is the leading cause of Spinal Cord injury in developing counties as compared to the developed ones. The current study was conducted to gauge the knowledge of first-aid among first responders in Delhi NCR. Materials and Methods: Two separate surveys with closed ended questions were formulated for the general public and first aiders in English and Hindi. A sample of 511 general public respondents with no medical training, and first aiders (108 ambulance and 201 police personnel) completed the survey between February 2019-April 2019. Data were analyzed descriptively and comparisons were made across demographic variables for the general public. For first aiders, comparisons were made between ambulance and police personnel across all sub-domains. Results: The average scores for all general public respondents were below 40% in all domains. Differences across age and educational qualification were small, yet significant. Ambulance personnel scored better than police personnel. But overall, the scores are poor for all first aiders. Conclusion: Pre-hospital trauma care needs to be strengthened through improving knowledge and providing training to both the groups for essential life saving skills within the 'golden hour'.